Strategy for Enhancing Quality of Labor through Technical Vocational Education & Training Faces Industry 4.0 Challenges - Nuraeni, Yeni; Suwadji, Yuniarti Tri (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
The field of Indonesian Manpower, the low competence of manpower makes it increasingly difficult for workers to find work. Vocational education which is more oriented on expertise and mastery of practice can be a solution to reduce unemployment and prepare workers in the Era of the Industrial Revolution 4.0 and global labor market competition. This study aims to analyze the readiness of the Indonesian government in improving the quality of human resources through technical vocational education and training. The research method used is descriptive qualitative. Primary data collection is done through FGD mechanism and questionnaire distribution. From the results of the study it can be concluded, reforms need to be made to the technical vocational education & training system, among them; relating to the provision of infrastructure and equipment to support the use of industry 4.0 technology, the creation of Vocational high School that have advantages and graduates needed by the labor market, avoiding overlaps between vocational high School, vocational training center and polytechnic, and the empowerment of associations, industry and society in improving the vocational system. Improvements to the technical vocational education & training system need to be supported by a sustainable funding system including through the Unemployment Benefit and Skill Development Fund